Analisis Strategi Tenaga Kerja untuk Meningkatkan Kinerja Karyawan pada PT. Itergo Buana Utama Bandung - Maysha Nakita Maharani Putri; Resya Dwi Marselina; Silfi Nur Fadilah; Sipa Maryana; Shopia Sri Mulyawati; Sulaini Hikmah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the workforce strategies implemented by PT. Itergo Buana Utama Bandung to improve employee performance in the surveying and mapping services industry. The study employs a descriptive qualitative approach, utilizing primary data obtained through in-depth interviews and field observations, as well as secondary data in the form of internal company documents and relevant literature. Informants were selected using purposive sampling, involving management and employees directly involved in project implementation. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions, validated through source and method triangulation. The research findings indicate that effective workforce strategies are built through periodic job rotation to enhance competency flexibility, the development of a self-directed learning culture to accelerate adaptation to digital technology, and the implementation of output-based performance management supported by an open rewards and evaluation system. A flexible organizational structure further strengthens the company’s ability to align workforce needs with project dynamics. The integration of these strategies contributes to improved productivity, work quality, adaptability, and operational effectiveness among employees, thereby supporting the sustainability of organizational performance in a dynamic business environment.